Penerapan Metode Bermain dalam Permainan Congklak untuk Meningkatkan Perilaku Sikap Jujur Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal II Perumnas - Eka Damayanti; M. Yusuf T; Nurannisa Nurannisa; Rismawati MS (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2022)
Moral development in children, especially the development of honest attitudes, is very important to be stimulated from an early age because it is the main basis for interacting with people around them. This study aims to determine the increase in the moral development of children, especially the honest behavior of children after the application of the game ofcongklak in children aged 5-6 years. This Community Service Research in the form ofService Learning was conducted at TKAisyiyah Bustanul Athfal Il Perumnas with a total of 4 children. The instruments used in data collection were observation sheets for children and implementation evaluation sheets using the play method using the game congklak. Data analysis used descriptive statistics. The results of this service research show that children are able to apply honest behavior. The findings in this study imply that the method of playing congklak can be applied by teachers or parents in teaching honest behavior to children aged 5-6 years.